Association Between Progressive Retinal Nerve Fiber Layer Loss and Longitudinal Change in Quality of Life in Glaucoma - Gracitelli, Carolina P. B. (JAMA Ophthalmol, 2015)
IMPORTANCE: Evaluation of structural optic nerve damage is a fundamental part of diagnosis and management of glaucoma. However, the relationship between structural measurements and disability associated with the disease is not well characterized. Quantification of this relationship may help validate structural measurements as markers directly relevant to quality of life. OBJECTIVE: To evaluate the relationship between rates of retinal nerve fiber layer (RNFL) loss and longitudinal changes in quality of life in glaucoma. DESIGN, SETTING, AND PARTICIPANTS: Observational cohort study including 260 eyes of 130 patients with glaucoma followed up for a mean (SD) of 3.5 (0.7) years. All patients had repeatable visual field defects on standard automated perimetry (SAP) at baseline. The 25-item National Eye Institute Visual Function Questionnaire (NEI VFQ-25) was performed annually, and spectral-domain optical coherence tomography and SAP were performed at 6-month intervals. A joint model was used to investigate the association between change in NEI VFQ-25 Rasch-calibrated scores and change in RNFL thickness, adjusting for confounding socioeconomic and clinical variables. MAIN OUTCOMES AND MEASURES: Association between change in binocular RNFL thickness (RNFL thickness in the better eye at each point) and change in NEI VFQ-25 scores. RESULTS: Progressive binocular RNFL thickness loss was associated with worsening of NEI VFQ-25 scores over time. In a multivariable model adjusting for baseline disease severity and the rate of change in binocular SAP sensitivity, each 1-μm-per-year loss of RNFL thickness was associated with a decrease of 1.3 units (95% CI, 1.02–1.56) per year in NEI VFQ-25 scores (P < .001). After adjusting for the contribution from SAP, 26% (95% CI, 12%–39%) of the variability of change in NEI VFQ-25 scores was associated uniquely with change in binocular RNFL thickness. The P value remained less than .001 after adjusting for potential confounding factors. CONCLUSIONS AND RELEVANCE: Progressive binocular RNFL thickness loss was associated with longitudinal loss in quality of life, even after adjustment for progressive visual field loss. These findings suggest that rates of binocular RNFL change are valid markers for the degree of neural loss in glaucoma with significant relationship to glaucoma-associated disability.